Metodologia para qualificação de equipamentos de radioscopia industrial - Beserra, Marcela Tatiana Fernandes (2018)
Industrial Radioscopy is a non-destructive testing method that employ ionizing radiation mainly X-rays. It provides real-time information on any imperfections found on a given specimen, thus offering a potential solution for the detection of failures and the improvement of products and production processes. The objective of this multidisciplinary study is to present a methodology for evaluating the performance of the component parts of Industrial Radioscopy equipment. The Computational Vision algorithms were developed in MATLAB, proposed the use of alternative testing standards, developed phantoms to evaluate systems performance, employed standards and traceable measurement equipment. The methodology was applied to Industrial Radioscopy equipment with Image Intensifier and Flat Panel detectors. Experimental tests were performed and were able to evaluate the performance of these systems under several criteria defined according to standards and specifications. The subsystem performance validation results enabled a more objective and robust evaluation, thus contributing to the guidelines suggested by ASTM E1411-16 related to the qualification of Industrial Radioscopy equipment.